Sistem Monitoring Detak Jantung Untuk Mendeteksi Tingkat Kesehatan Jantung Berbasis Internet Of Things Menggunakan Android - Jarot Dian; Fujiama Diapoldo Silalahi; Nuris Dwi Setiawan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
The heart is a vital human organ that has an important role. Human heart rate is also an important factor in determining a person's level of health. A slow or fast heart rate will have a negative impact on a person's health. To find out if the heart rate is still beating normally or not, then measurements are taken, both measurements with experts and with heart rate measuring instruments. The adult heart rate ranges from 60-100 bpm. Through technological developments in telecommunications systems, users can obtain the desired information. One of these technological developments is the use of a microcontroller that can control or send data via sensors. From the above background, the author makes a system or tool that can monitor the heart rate to detect the level of health. This system utilizes a wemos microcontroller and a pulse sensor that will read the heart rate beats per minute.